Implementing Zakat Core Principles in Zakat Distribution Governance: A Case Study of Al Azhar Zakat Institution, Indonesia - Umi Qulsum; Ade Nur Rohim (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2026)
Indonesia has enormous zakat potential with the capacity to contribute significantly to the national economy if managed optimally. In practice, the governance of zakat distribution remains suboptimal and continues to pose a major challenge for zakat institutions. One contributing factor is the limited understanding and partial implementation of the Zakat Core Principles (ZCP) within zakat institutions. This study aims to examine the implementation of the ZCP in zakat distribution governance at LAZ Al Azhar. This research employs a descriptive qualitative method with a case study approach and content analysis techniques. Primary data were collected through interviews, observations, and documentation, while secondary data were obtained from official websites, books, academic journals, and the institutional profile of LAZ Al Azhar. The collected data were analyzed using thematic coding to identify patterns and insights regarding the implementation of the ZCP criteria. The findings reveal that LAZ Al Azhar has implemented the ten ZCP criteria, including transparency, accountability, efficiency, effectiveness, and strong supervisory mechanisms, which support the optimal attainment of zakat objectives. This study fills the gap in the empirical assessment of ZCP implementation at the institutional level in Indonesia. The implementation of the ZCP serves as a crucial reference for strengthening zakat governance across zakat management organizations in Indonesia.